The Effect Of Range Of Motion (ROM) Exercises On Sensory Function And Ankle Brachial Index In Diabetes Mellitus Patients At Tamamaung Health Center, Makassar - Asnaniar, Wa Ode Sri; Abri, Putri Damayanti; Padhila, Nur Ilah; Ernasari, Ernasari (International Journal of Halal System and Sustainability https://jurnal.narotama.ac.id/https://www.spb.gba.gov.ar/campus/https://conference.trunojoyo.ac.id/https://ojs.ucp.edu.ar/https://libros.cimsur.unam.mx/https://ojs.stikesmucis.ac.id/http://medi, 2023)
The problem that often occurs in Diabetes Mellitus is peripheral neuropathy. Peripheral neuropathy can cause sensory sensations in the legs to decrease or even disappear. Flow disturbances in the legs could be detected by measuring the ankle brachial index (ABI), which measures the ratio of the systolic pressure in the arm to the systolic pressure of the lower leg. One of tnon-pharmacological therapy is lower range of motion (ROM). This study aimed to determine whether there is an effect of Range of Motion (ROM) exercise on sensory function and Ankle brachial Index in DM patients. This study was conducted in Tamamaung Health Center, Makassar. It used pre-experimental research method in the form of one-group pretest-posttest design. It was conducted with direct observation by the researchers. The research sample was 15 respondents at Tamamaung Health Center Makassar who met the criteria of inclusion. Analysis of the data used Wilcoxon Signed Ranks test and Paired Sample T-Test. Results of sufficient analysis showed the effect of range of motion exercise on the sensory function and Ankle brachial index in DM patients at Tamamaung Health Center, Makassar. The sensory function was tested using Wilcoxon Signed Ranks test and obtained the value of ρ = 0.001, indicating that value of ρ was smaller than α = 0.05. Thus, for the sensory function, Ha was accepted and H0 was rejected. In addition, the right ABI value was tested using Wilcoxon Signed Ranks Test and obtained the value of ρ = 0.001, while the left ABI value was tested using Paired Sample T Test and obtained the value of ρ = 0.000, indicating that the value of ρ was smaller than α = 0.05. It means that for ABI value, Ha was accepted and H0 was rejected. The results concludes that there is an effect of range of motion exercise on sensory function and Ankle brachial index in diabetes mellitus patients at Tamamaung Health Center, Makassar. It is recommended that there should be educational program and implementation of ROM exercises especially in diabetes mellitus patients.